Accumulation of legacy fallout radionuclides in cryoconite on Isfallsglaciären (Arctic Sweden) and their downstream spatial distribution - C. C. Clason (Copernicus Publications, 2021)
The release of legacy contaminants such as fallout radionuclides (FRNs) in response to glacier retreat is a process that has received relatively little attention to date, yet may have consequences as a source of secondary contamination as glaciers melt and down-waste in response to a warming climate. The presence of FRNs in glacier-fed catchments is poorly understood in comparison to other contaminants, yet there is now emerging evidence from multiple regions of the global cryosphere for substantially augmented FRN activities in cryoconite. Here we report concentrated FRNs in both cryoconite and proglacial sediments from the Isfallsglaciären catchment in Arctic Sweden. Activities of some FRNs in cryoconite are 2 orders of magnitude above those found elsewhere in the catchment, and above the activities found in other environmental matrices outside of nuclear exclusion zones. We also describe the presence of the short-lived cosmogenic radionuclide 7Be in cryoconite samples, highlighting the importance of meltwater–sediment interactions in radionuclide accumulation in the ice surface environment. It is currently unknown whether high accumulations of fallout radionuclides in glaciers have the potential to impact local environmental quality through down-wasting and downstream transport of contaminants to the proglacial environment through interaction with sediments and meltwater. We thus recommend that future research in this field focusses on processes of accumulation of FRNs and other environmental contaminants in cryoconite and whether these contaminants are present in quantities harmful for downstream ecosystems.